2010
DOI: 10.1039/c0ay00288g
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative analysis of retinol, retinyl esters, tocopherols and selected carotenoids out of various internal organs from different species by HPLC

Abstract: We report the validation of a reversed-phase gradient HPLC method allowing simultaneous quantification of retinol, retinyl esters, tocopherols and selected carotenoids in lung, liver and plasma of mouse, rat and guinea pig (gp) using a diode array detector. A significant species difference was observed regarding the distribution of retinol and retinyl esters. The levels of total retinol in lung, liver and plasma were in the following order: mouse >> rat > gp; rat >mouse > gp; and gp >> rat > mouse, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…GPx activity was assessed with a commercially available kit (BioVision, Milpitas, CA, USA), while α-tocopherol levels were determined by LC-FL. 16) Previous studies reported that hepato-renal α-tocopherol was positively correlated with TG. 17,18) Hence, in this study, hepatorenal α-tocopherol levels were expressed as the ratio of α-tocopherol to TG.…”
Section: Chemicalsmentioning
confidence: 99%
“…GPx activity was assessed with a commercially available kit (BioVision, Milpitas, CA, USA), while α-tocopherol levels were determined by LC-FL. 16) Previous studies reported that hepato-renal α-tocopherol was positively correlated with TG. 17,18) Hence, in this study, hepatorenal α-tocopherol levels were expressed as the ratio of α-tocopherol to TG.…”
Section: Chemicalsmentioning
confidence: 99%
“…Recent work in our laboratory indicates that rodent species such as mouse and rat differ significantly in their lung vitamin A profile in comparison to guinea pig and human, which show a remarkable similarity [18]. This raises the question whether substantial changes also exist in the detailed regulation of the vitamin A signaling pathway and RA-dependent gene expression, which in turn would still leave the question open if inhaled ATRA can prevent, alter, or abrogate pathological conditions in lung cancer, chronic lung obstructive pulmonary disease (COPD), and emphysema.…”
Section: Discussionmentioning
confidence: 99%
“…Preparations were carried out under dim yellow light, and aliquots frozen at −80°C. HPLC-analyses and sample extractions were performed as reported earlier [18]. According to the manufacturer PARI, the mass median diameter for a typical aerosol is 2.9 micron in a PARI LC Star nebulizer driven by a PRONEB Ultra Compressor.…”
Section: Methodsmentioning
confidence: 99%
“…The intrinsic fluorophore standards were purchased from Sigma Aldrich (St. Louis, MO), and their concentrations in solutions were determined by UV–VIS spectrophotometry using the extinction coefficients supplied by the manufacturer or from the literature [31,32]. Retinol and all-trans retinoic acid (catalog #R7632 and #R2625) were prepared in DMSO at concentrations of 0.13 mM and 46 mM, respectively.…”
Section: Methodsmentioning
confidence: 99%